Ultrasonographic Evaluation of Intestinal Fibrosis and Inflammation in Crohn’s Disease. The State of the Art - Ferretti, Francesca; Cannatelli, Rosanna; Ardizzone, Sandro; Maier, Jeanette A.; Maconi, Giovanni (Frontiers in Pharmacology, 2021)
The evaluation of the degree of inflammation and fibrosis, intrinsic elements in intestinal wall damage of Crohn's disease, is essential to individuate the extent of the lesions and the presence of strictures. This information will contribute to the choice of the appropriate therapeutic approach, the prediction of the response to therapy and the course of the disease. The accurate evaluation of the extent and severity of inflammation and/or fibrosis in Crohn's disease currently requires histopathological analysis of the intestinal wall. However, in clinical practice and research, transmural assessment of the intestinal wall with cross sectional imaging is increasingly used for this purpose. The B-mode ultrasonograhic characteristics of the intestinal wall, the assessment of its vascularization by color Doppler and I.V. contrast agents, and the evaluation of the mechanical and elastic properties by sonoelastography, may provide useful and accurate information on the severity and extent of inflammation and intestinal fibrosis in Crohn's disease. The purpose of this review is to provide an update on current sonographic methods to discriminate inflammation and fibrosis in Crohn's disease.